Pengaruh Modifikasi Rocking Pelvic Terhadap Percepatan Kala I Persalinan Pada Ibu Primigravida - Nurdin, St Surya Indah; Asikin, Zulaika F; Ahmad, Zul Fikar (Madu : Jurnal Kesehatan, 2023)
Pelvic rocking is an exercise that moves the pelvis or swings and shakes it forward and backward; the right side, left, and circular will feel more relaxed and facilitate the opening of the birth canal during labor. This study aimed to determine the effect of Pelvic Rocking modification on the progress of first-stage labor at Siti Khadijah Gorontalo City. Pelvic rocking modification is expected to provide better results in labor progress in the first stage. This study was conducted at the Sitti Khadijah Mother and Child Hospital, Gorontalo City. This study used a quasi-experimental design with a post-test-only control group design. All primigravida inpartu mothers were in the study population with a sample size 50. The results showed that the p-value of 0.036 < α (0.05) there was an effect of Pelvic Rocking modification on the progress of labor in the first phase of the active phase in mothers who were given pelvic rocking modification and those who were not given pelvic rocking.